Analisis Korelasi Antara Pajak Ekspor dan Nilai Ekspor di Indonesia (Periode 1987-2007) - Sukarsih Sukarsih; Diah Gunawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2012)
This research aim to know the existence of correlation between export tax (as a transaction cost in export transaction) and export value in Indonesia. This research used secondary data (export tax earning and export value) with time period between 1987-2007. Analysis tool in this research involve descriptive analysis and paired samples correlations. Based on the analysis result, there’s no correlation between export tax and export value. Even there’s no correlation between export tax and export value, government as policy maker must consider about export tax. Export tax may not pursue export transaction. Keywords: transaction cost, export tax, export value